Rezension: Filder, Harald (2023). So funktioniert Österreichs Medienwelt. Wien: Falter Verlag - Birkner, Thomas (medien & zeit. Kommunikation in Vergangenheit und Gegenwart, 2024)
Filder, Harald (2023). So funktioniert Österreichs Medienwelt. Wien: Falter Verlag, 232 Seiten